“Role models can’t just be on posters”: Re/membering Barriers to Indigenous Community Engagement - Madden, Brooke; Higgins, Marc; Korteweg, Dr. Lisa (Canadian Journal of Education/Revue canadienne de l’éducation, 2013)
Current Canadian scholarly literature, education policy, and curricular documents encourage the participation of Indigenous community members as a key component of Indigenous Education reform. Guided by sharing circles conducted with Indigenous Elders, families, teachers, and support workers, we present community voices and experiences of Indigenous Education in an urban school board through poetic transcription. Our research suggests that four key barriers will have to be overcome in efforts to improve urban Indigenous Education: unwelcoming schools, professionalization of classroom teaching, colonized classrooms, and unilateral decolonization. Poetic transcription is used in this article to centre the voices of Indigenous participants as well as attempt to decolonize our approach to data dissemination of Indigenous voices as white, Euro-Canadian university-based researchers. La littérature savante, les politiques d’éducation et les documents curriculaires canadiens actuels encouragent la participation des membres des communautés autochtones comme élément-clé de la réforme en matière d’éducation autochtone. À partir des cercles de partage auxquels participaient les aînés, les familles, les enseignants et les agents de soutien, nous présentons, par l’intermédiaire de la transcription poétique, les voix et les expériences d’une communauté autochtone en milieu scolaire urbain. Notre recherche suggère quatre barrières à surmonter dans le but d’améliorer l’expérience scolaire en milieu urbain : écoles non accueillantes, professionnalisation de l’enseignement en salle de classe, salle de classe colonisée et décolonisation unilatérale. L’utilisation de la transcription poétique dans cet article a comme objectif de mettre en valeur les voix des participants de la communauté autochtone et de tenter de décoloniser, à titre de chercheurs universitaires blancs euro-canadiens, notre approche de dissémination des données reliées aux voix autochtones.